PENGUATAN KARAKTER MAHASISWA FASIH DIDALAM PANCASILA SEBAGAI IDEOLOGI BANGSA - Devra, Desi Devrika; Febrian, Albet (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Pancasila, as an Indonesian belief system, is closely related to the bangsa and national way of life. Pancasila, which is composed of several principles, is, in fact, a philosophical system.One of the characteristics of an open ideology is that the values and ideals of the struggle are obtained and dug from the spiritual resources, morals, and culture of their own people rather than being isolated from the outside world. Keywords: The doctrine of Pancasila